2022
DOI: 10.3233/ch-221487
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound features of abdominal thrombosis in COVID 19 patients

Abstract: Purpose: Abdominal thromboses are a poorly characterized thrombotic complication of COVID-19. The aim of this paper is to report multimodality ultrasound imaging findings of the abdomen in evaluation of thrombotic lesions in hospitalized patients with COVID-19. Patients & Methods: In this retrospective observational study, patients admitted to a single University Hospital from April 1, 2020 to April 30, 2022, who tested positive for COVID-19 and developed acute abdominal pain over the course of hospitaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…CTV and contrast enhanced ultrasound (CEUS) are both often used method for the detection of venous thromboses [ 20 ]. CEUS can sensitively depict the microcirculation perfusion within the tissue, overcoming the disadvantage of color ultrasound is difficult to show fine blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…CTV and contrast enhanced ultrasound (CEUS) are both often used method for the detection of venous thromboses [ 20 ]. CEUS can sensitively depict the microcirculation perfusion within the tissue, overcoming the disadvantage of color ultrasound is difficult to show fine blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that hospitalised COVID-19 patients can experience thromboembolic consequences. The early and precise diagnosis of these issues can be achieved with multimodality ultrasound tests [28].…”
Section: Effect Of Sars-cov-2 On Thrombotic Processes In the Whole Bo...mentioning
confidence: 99%
“…COVID-19 distinguishes itself by oscillation between thrombotic and fibrinolytic phase which leads to micro and macro thrombi and consumption of important products for coagulation [4][5][6]. This high build up and lysis of thrombi [7,8] is shown by highly elevated d-dimers and a steady consumption of fibrinogen. Elevated d-dimers on admission in COVID-19 patients are associated with worsen prognosis 12].…”
Section: Introductionmentioning
confidence: 99%